Physiological characteristics associated with W' and W'bal used during intermittent exercise task to failure - Welburn, A.; Bailey, S.; Pugh, C.; Ferguson, R. (Journal of Science and Cycling, 2023)
The critical power (CP) and W' concept has become more integrated within applied cycling performance assessment. Both parameters can be tested for in the laboratory and field and have thus become a useful tool for coaches and athletes. The development of the Wbal concept allows us to mathematically model the depletion and recovery of W' (Skiba et al., 2012, Skiba and Clarke, 2021). When exercising above CP, there is a proposed linear utilisation of W'. When exercising below CP, W' is reconstituted (W'rec). When W' has been fully utilised and Wbal (the balance between utilisation and reconstitution) reaches 0, it is assumed exhaustion will occur.